2023
DOI: 10.3389/fcimb.2023.1159455
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the microbiota of cleft lip and palate patients: a comprehensive review

Abstract: Orofacial cleft disorders, including cleft lip and/or palate (CL/P), are one of the most frequently-occurring congenital disorders worldwide. The health issues of patients with CL/P encompass far more than just their anatomic anomaly, as patients with CL/P are prone to having a high incidence of infectious diseases. While it has been previously established that the oral microbiome of patients with CL/P differs from that of unaffected patients, the exact nature of this variance, including the relevant bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 140 publications
0
3
0
Order By: Relevance
“…This systematic review presents a comprehensive analysis of the oral microbiota in children with CLP. In light of the increased prevalence of dental caries in these children [ 37 ], it is essential to analyze how the oral microbiota of children with CLP differs from the microbiological status of the healthy population without cleft, as well as which bacterial species, particularly those associated with caries, may be associated with the plaque biofilms formed on the teeth of these patients [ 38 ]. Twelve studies investigating the microbiological status of CLP individuals compared to non-cleft individuals were included in the review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review presents a comprehensive analysis of the oral microbiota in children with CLP. In light of the increased prevalence of dental caries in these children [ 37 ], it is essential to analyze how the oral microbiota of children with CLP differs from the microbiological status of the healthy population without cleft, as well as which bacterial species, particularly those associated with caries, may be associated with the plaque biofilms formed on the teeth of these patients [ 38 ]. Twelve studies investigating the microbiological status of CLP individuals compared to non-cleft individuals were included in the review.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the presence of malocclusions and structural abnormalities, including changes in tooth number, position, and morphology, further complicate oral hygiene maintenance. These issues are often accompanied by long orthodontic treatments, which can prolong the challenges faced by these patients in maintaining good oral hygiene [ 12 , 14 , 15 , 26 , 38 , 52 ]. Furthermore, fixed orthodontic appliances, such as bands and braces, pose additional challenges to oral hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…This randomized clinical trial was designed to compare the effects of mechanical and chemical cleansing methods on bacterial biofilm attached to acrylic-based removable orthodontic appliances. It was reported that the prevalence of opportunistic pathogens was higher in PMMA-based intraoral devices such as feeding appliances in cleft lip and palate patients, orthodontic retainers, and prosthodontic prostheses [ 7 , 25 , 26 ]. Previous studies compared the mechanical or chemical cleaning methods solely on biofilm-removing efficacy [ 27 ]; however, to the author's knowledge, no information was available on the effects of polishing the fitting surface of the acrylic-based orthodontic appliances on biofilm reduction using these cleaning methods apart from a laboratory-based attempt to reduce the amount of biofilm by modifying the surface texture of these appliances using an artificial mouth device, i.e., the constant depth film fermenter [ 18 ].…”
Section: Discussionmentioning
confidence: 99%